p53 Expression, Programmed Death Ligand 1, and Risk Factors in Urinary Tract Small Cell Carcinoma - Golijanin, Borivoj; Gershman, Boris; De Souza, Andre; Kott, Ohad; Carneiro, Benedito A.; Mega, Anthony; Golijanin, Dragan J.; Amin, Ali (Frontiers in Oncology, 2021)
Introduction: Small cell carcinoma of the urinary tract (SCCUT) is a rare finding with poor clinical course. This study sheds light on the molecular subtype and identifies risk factors in patients diagnosed with SCCUT. Methods: Immunohistochemical expression of immunotherapy target programmed death ligand 1 (PD-L1) and luminal (GATA3), basal (p63), and p53 markers are assessed in patients diagnosed with SCCUT. Univariate analysis identified risk factors. Overall survival (OS) is computed using the Kaplan–Meier method. Results: Tissue was available for 70.2% (33/47). All showed a high PD-L1 expression phenotype. p53 is seen in 93.9% (31/33), mostly as overexpression, GATA3 in 45.5% (15/33), and p63 in 57.6% (19/33). For the entire cohort (n = 47), 1-year survival was 59.6%, and the median OS was 17 months. Univariate analysis shows that chemotherapy [hazard ratio (HR) = 0.29, 95% confidence interval (CI) = 0.14–0.61, p = 0.001], radical surgery (HR = 0.37, 95% CI = 0.18–0.76, p = 0.007), and diagnosis of non-pure SCCUT (HR = 0.44, 95% CI = 0.22–0.86, p = 0.02) are favorable prognostic features. Metastasis had negative associations with survival (HR = 2.1, 95% CI = 1.1–4.2, p = 0.03). Conclusions: In this series, pure and mixed SCCUT are characterized by p53 overexpression and a high PD-L1 phenotype. Histology of non-pure SCCUT is a positive prognosticator, and radical cystectomy or chemotherapy can improve OS. These findings demonstrate that SCCUT may be eligible for PD-L1 immunotherapy.